2021
DOI: 10.1007/s13555-021-00617-6
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Infants, Toddlers and Preschoolers with Seborrhoeic, Allergic Contact and Atopic Dermatitis Before and During COVID-19 Pandemic

Abstract: Introduction Different aspects of quality of life (QoL) of infants and children with atopic dermatitis (AD) are well studied but there is a lack of studies on seborrhoeic dermatitis (SD) and allergic contact dermatitis (ACD). The aim of this study was to compare the impact of SD, ACD and AD on young children. Parts of questionnaires were filled in during the COVID-19 pandemic and therefore we decided to check if the pandemic affected dermatology-specific health-related quality of life (HRQoL) in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“… 22 Finally, external factors as in case of the COVID-19 pandemic may have multidirectional effects on patient’s HRQoL. 3 , 23 Similar to our study the person who fills-in the proxy- ratings in most cases is the mother. 24 However, no significant difference between mothers’ and fathers’ assessment of AD-specific proxy questionnaire was previously reported.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“… 22 Finally, external factors as in case of the COVID-19 pandemic may have multidirectional effects on patient’s HRQoL. 3 , 23 Similar to our study the person who fills-in the proxy- ratings in most cases is the mother. 24 However, no significant difference between mothers’ and fathers’ assessment of AD-specific proxy questionnaire was previously reported.…”
Section: Discussionsupporting
confidence: 66%
“… 2 The InToDermQoL was used to study QoL in children with seborrheic, allergic contact, and atopic dermatitis (AD) before and during COVID-19 pandemic. 3 An epidermolysis bullosa-specific module of the InToDermQoL was developed and underwent initial validation separately. 4 , 5 , 6 …”
Section: Introductionmentioning
confidence: 99%
“…In line with this observation, in the present research, a statistically significant relationship was determined between the number of new-onset acne vulgaris cases and the median duration of mask wearing in a day (p=0.025). In another study investigating the effects of Covid-19 pandemic upon dermatologyspecific health-related quality of life (HRQoL) in pediatric patients aged between 0-4 years, it was revealed that patients with SD and allergic contact dermatitis had a comparable but lower influence of cutaneous diseases on their HRQoL when compared with children with atopic dermatitis [22]. Even though, HRQoL is not evaluated in our study, the exacerbation of the skin disease was observed in 32 patients with SD and 5 patients with atopic dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“… 10 12 Nevertheless, few studies have examined the association of the COVID-19 pandemic and HRQoL outcomes in AD patients. 13 15 …”
Section: Capsule Summarymentioning
confidence: 99%
“…[10][11][12] Nevertheless, few studies have examined the association of the COVID-19 pandemic and HRQoL outcomes in AD patients. [13][14][15] Skin-specific and generic questionnaires are extensively used to measure HRQoL in adult AD patients. 16 Skin-specific instruments allow comparisons across different skin conditions and are typically more sensitive to HRQoL changes related to the skin disease.…”
mentioning
confidence: 99%